A STUDY OF THE IMPLEMENTATION OF PAIKEM LEARNING ACTIVITIES AT GRADE II SDN SEROJA - Mutia Kanza; M. Hosnan, Suparno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by learning activities whose implementation still used the lecture method. Many teachers were less creative in managing learning so that learning seems monotonous and only teacher-centered. In addition, students seemed to be passive during learning activities. Based on these problems, the objectives of this research were the plan, process, and result of PAIKEM learning at grade II SDN Seroja. The method in this research was qualitative research with a descriptive approach carried out at SDN Seroja. Data were collected through interview, observation, and documentation. The subjects of this research were chosen through purposive sampling, which were grade II students at SDN Seroja. Then, the data were analyzed through qualitative descriptive analysis. The results of this research revealed that the implementation of PAIKEM learning activities was good enough, capable, and gave good impacts.